2021
DOI: 10.1080/03043797.2021.1903835
|View full text |Cite
|
Sign up to set email alerts
|

Developing growth mindsets in engineering students: a systematic literature review of interventions

Abstract: Dropout from engineering studies has been linked to 'fixed mindset' beliefs of intelligence as fixed-at-birth that make students more likely to disengage when facing new challenges. In contrast, 'growth mindset' beliefs that intelligence can be improved with effort make students more likely to persist when confronting difficulties. This systematic literature review of engineering, education and psychology databases explores the effectiveness of different interventions in developing growth mindset in engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 49 publications
0
14
1
Order By: Relevance
“…We can say that whether a student has achieved his/her higher secondary education from a rural area or from an urban area will not make any difference in their academic performance at higher education level. These results contradict those of Campbell et al (2021), Gilal et al (2018), andSofo et al (2009), who found that students' geographic location had a significant impact on their academic success and other behavioral reactions. Furthermore, moderation effect for medium of instruction in the higher secondary school revealed that the students who have achieved their higher secondary education from non-English medium school perform better at higher education level than those students who have studied from an English medium school.…”
Section: Findings and Discussioncontrasting
confidence: 76%
“…We can say that whether a student has achieved his/her higher secondary education from a rural area or from an urban area will not make any difference in their academic performance at higher education level. These results contradict those of Campbell et al (2021), Gilal et al (2018), andSofo et al (2009), who found that students' geographic location had a significant impact on their academic success and other behavioral reactions. Furthermore, moderation effect for medium of instruction in the higher secondary school revealed that the students who have achieved their higher secondary education from non-English medium school perform better at higher education level than those students who have studied from an English medium school.…”
Section: Findings and Discussioncontrasting
confidence: 76%
“…e study of the relative validity of each basic unit facilitates the improvement of the experimental management model and the development of rational planning, thus maximizing the effectiveness of experimental design [23]. Scientific measurement of experimental design validity can reflect the degree of effective subjective efforts to improve experimental design, which can have a motivating effect on each unit [24]. For measuring the effectiveness of teaching experimental design, hierarchical analysis has been used in the past to analyze the good and bad experimental design of each unit.…”
Section: Treating Quasi-conclusion As Conclusivementioning
confidence: 99%
“…This is an expected result, as not all mechanisms should be expected to generate universal outcomes. A literature review of growth mindset studies involving engineering students (Campbell et al, 2021) proposed promising but similarly mixed conclusions based on population group. These results provide the framework for future studies.…”
Section: Growth Mindset Relevance In Higher Educationmentioning
confidence: 99%